Complexometric Determination of Thallium(III) Using Bromide as Masking Agent and Silver(I) as Demasking Agent - Muralidhara Rao, B. (Asian Journal of Chemistry, 2010)
Thallium(III) ions (4-40 mg) in presence of co-ions are treated with excess of bromide (0.05 M) and followed by excess of EDTA (0.02 M). The surplus EDTA is titrated with zinc sulphate solution using xylenol orange as an indicator at pH 5-6 (hexamine). Bromide complex of thallium(III) is then demasked using silver nitrate solution. Thallium(III) free from bromide ion is then titrated with EDTA to the end point violet to yellow. Reproducible and accurate results are obtainable with relative errors £ 0.5 % and standard deviations £0.05 mg.